2020
DOI: 10.3390/nano10091859
|View full text |Cite
|
Sign up to set email alerts
|

Abatement of the Stimulatory Effect of Copper Nanoparticles Supported on Titania on Ovarian Cell Functions by Some Plants and Phytochemicals

Abstract: The application of nanoparticles has experienced a vertiginous growth, but their interaction with food and medicinal plants in organisms, especially in the control of reproduction, remains unresolved. We examined the influence of copper nanoparticles supported on titania (CuNPs/TiO2), plant extracts (buckwheat (Fagopyrum esculentum) and vitex (Vitex agnus-castus)), phytochemicals (rutin and apigenin), and their combination with CuNPs/TiO2 on ovarian cell functions, using cultured porcine ovarian granulosa cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(26 citation statements)
references
References 63 publications
1
25
0
Order By: Relevance
“…The comparison of the effects of elderberry extract and rutin showed the similar effects for the extracts and its major component. In experiments of Sirotkin et al [8,89], the addition of rutin was found to increase the viability of cultured porcine ovarian granulosa cells, although this effect was not associated with changes in the accumulation of markers of proliferation (accumulation of PCNA) and cytoplasmic apoptosis (Bax). In vivo experiments, like in vitro ones, demonstrated the stimulatory action of rutin on rat ovarian cell health and ovarian folliculogenesis [90,91].…”
Section: Effect Of Elderberry and Its Constituents On Ovarian Cell Vi...mentioning
confidence: 88%
See 2 more Smart Citations
“…The comparison of the effects of elderberry extract and rutin showed the similar effects for the extracts and its major component. In experiments of Sirotkin et al [8,89], the addition of rutin was found to increase the viability of cultured porcine ovarian granulosa cells, although this effect was not associated with changes in the accumulation of markers of proliferation (accumulation of PCNA) and cytoplasmic apoptosis (Bax). In vivo experiments, like in vitro ones, demonstrated the stimulatory action of rutin on rat ovarian cell health and ovarian folliculogenesis [90,91].…”
Section: Effect Of Elderberry and Its Constituents On Ovarian Cell Vi...mentioning
confidence: 88%
“…In vivo and in vitro studies on rats demonstrated the ability of rutin to promote the plasma luteinizing hormone (LH) level, expression of ovarian follicle-stimulating hormone (FSH) receptors, steroidogenic enzymes, ovarian folliculogenesis and fecundity [90,91]. In in vitro experiments with cultured porcine granulosa cells, the addition of rutin was able to promote 17β-estradiol and testosterone, but not progesterone release [8,89,97]. It is not to be excluded that the increase in granulosa cell viability under the influence of elderberry extract could be due to the upregulation of estradiol, a known promoter of ovarian cell viability and ovarian folliculogenesis [98].…”
Section: Effect Of Elderberry and Its Constituents On Ovarian Cell St...mentioning
confidence: 99%
See 1 more Smart Citation
“…In some experiments of Sirotkin, Radosová, et al. (2020); Sirotkin et al. (2021) addition of rutin increased the viability of cultured porcine ovarian granulosa cells, although this effect was not associated with changes in accumulation of markers of proliferation (accumulation of PCNA) and cytoplasmic apoptosis (bax).…”
Section: Effects On Female Reproductive Processesmentioning
confidence: 96%
“…Most recently, Copper nanoparticles have also been studied in rapport with animals, namely how copper nanoparticles supported on titania might impact and influence the porcine ovarian cells [79]. The study concluded that the copper nanoparticles not only had a benefic impact on the granulosa ovarian cells, but also increased ovarian cell proliferation, turnover, viability and hormone release.…”
Section: Toxicity In Animalsmentioning
confidence: 99%